Unequal Positions: A Relational Approach to Racial Inequality Trends in the US States, 1940–2010. Issue 1 (7th December 2018) - Bruch, Sarah K.; Rosenthal, Aaron J.; Soss, Joe
Abstract : Racial inequality remains a painful and central feature of daily life in the United States. Yet few would deny that decades of political struggle have transformed the nation's racial landscape. In this article, we seek to advance long-standing sociological efforts to disentangle this braiding of persistence and change. Specifically, we intervene in two ways designed to build on national studies of inequality trends for black and white Americans. First, by shifting measurement to the state level, we reveal distinctive subnational trajectories and dynamics of convergence that have been obscured by the field's emphasis on aggregate national trends. Second, by drawing on relational theories of boundaries and positions, we develop a new empirical strategy for measuring racial inequalities over time. Identifying two key analytic dimensions (exclusion and subordination), we analyze the relative positions of whites and blacks in two domains (work and housing) across the decades from 1940 to 2010. Our results suggest that racial inequalities rooted in boundary-based dynamics of social closure (exclusion) proved far more durable than inequalities tied to inferior positions alone (subordination). Moreover, we find evidence of a significant nationalization of racial relations, with subnational units converging on a more uniform structure of racialized relations over time. We conclude that the period from 1940 to 2010 was marked by a "consolidation" of racial exclusion (i.e., convergence around relatively stable levels of inequality) paired with the comparatively greater "equalization" of racial subordination (i.e., stronger convergence around more substantial declines).